Yersinia enterocolitica in Crohn’s disease - Fang, Xue; Kang, Le; Qiu, Yi-Fan; Li, Zhao-Shen; Bai, Yu (Frontiers in Cellular and Infection Microbiology, 2023)
Increasing attention is being paid to the unique roles gut microbes play in both physiological and pathological processes. Crohn’s disease (CD) is a chronic, relapsing, inflammatory disease of the gastrointestinal tract with unknown etiology. Currently, gastrointestinal infection has been proposed as one initiating factor of CD. Yersinia enterocolitica, a zoonotic pathogen that exists widely in nature, is one of the most common bacteria causing acute infectious gastroenteritis, which displays clinical manifestations similar to CD. However, the specific role of Y. enterocolitica in CD is controversial. In this Review, we discuss the current knowledge on how Y. enterocolitica and derived microbial compounds may link to the pathogenesis of CD. We highlight examples of Y. enterocolitica-targeted interventions in the diagnosis and treatment of CD, and provide perspectives for future basic and translational investigations on this topic.